Hubungan Lingkar Panggul dan Body Condition Score (BCS) Terhadap Littersize Domba di PT. Sedana Peternak Sentosa Jombang Jawa Timur - Rukmi, Dyah Laksito; Qalbi, Aditya Amru Abrori; Hasanah, Niswatin; Utomo, Budi (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the relationship between pelvic circumference and Body Condition Score (BCS) to litter size of sheep at PT. Sedana Peternak Sentosa, Jombang, East Java, on August 18 - November 20, 2024. The research method used 35 female sheep aged 1.5-2 years with healthy criteria and had given birth, with a purposive sampling technique. Data analysis used the Spearman rank correlation test on SPSS version 25. The results showed an average pelvic circumference of 99.09 cm, BCS 4.51, and litter size 1.60. Statistical analysis revealed no significant relationship between pelvic circumference and BCS to litter size (very weak correlation, p>0.05). The low determination value (R² 4.2–4.9%) indicated the dominance of other factors such as genetics, environment, stud quality, and increased parity. This finding is thought to be related to the relatively young age of the sheep (1.5–2 years) with limited birth experience.